RESULTS OF LAPAROSCOPIC TREATMENT OF POSTOPERATIVE INTRAPERITONEAL BLEEDING - Yusubov, I.A. (World of Medicine and Biology, 2022)
The effectiveness of endovideosurgical treatment of intra-abdominal bleeding after abdominal operations was compared. The main group (n=85) included patients who underwent endovideosurgery for early postoperative bleeding, and the control group (n=44) included patients who used traditional methods of surgical correction. In 85 patients of the main group, laparoscopic hemostasis was attempted by clipping, suturing, electrocoagulation and joint methods. In the control group, a traditional relaparotomy was performed. Laparoscopy made it possible to avoid relaparotomy in 67 (78.8 %) of 85 patients, as well as to exclude intra-abdominal bleeding in 7 (8.2 %) patients. Indications for relaparotomy were revealed in 11 (12.9 %) observations during diagnostic laparoscopy. The average duration of laparoscopic surgery in the main group (33.1±22.8 min) was significantly reduced compared to the duration of relaparotomy in the control group (72.4±28.4 min). The lethal outcome in the control group was 4.5 % (2/44). No deaths were registered in the main group. The use of laparoscopy in the diagnosis and treatment of postoperative intra-abdominal bleeding does not exclude traditional surgical interventions and should be used if laparoscopic treatment is impossible or ineffective.
Keywords: postoperative complications; intra-abdominal bleeding; endoscopic treatment; endovideosurgery; laparoscopic hemostasis